Circular futures of the cement and concrete industry in the European Union: enriching prospective life cycle assessment with participatory foresight - Anna M. Walker; Cristian Matti; Paola Federica Albizzati; Leonidas Milios; Davide Tonini (The International Journal of Life Cycle Assessment, 2026)
Purpose Given the urgency of the cement and concrete industry to decarbonise by 2050, circular economy (CE) strategies are becoming more eminent. This study aims to identify how CE practices can contribute to lowering environmental impacts and in particular greenhouse gas (GHG) emissions in the European Union. As future developments of our socio-economic systems are inherently uncertain, the analysis also considers the effectiveness of CE measures in different types of decarbonised futures. Methods As part of a prospective LCA (pLCA), the study defines a status quo, a future baseline scenario with a decarbonised energy system and an ambitious circular economy scenario. These are then assessed using the Environmental Footprint (EF 3.1) method for the years 2030 and 2050. To account for the inherently higher epistemic uncertainty in 2050, the ambitious CE scenario is subjected to a sensitivity analysis consisting of four normative socio-economic scenarios on the green transition. The quantification of these alternative future narratives is achieved by means of a stakeholder workshop and sensemaking session. In a final step, the results of the pLCA following the historical trajectory and the ones of the alternative futures are compared and contextualised with the agency of the involved actors. Results and discussion Results indicate that the ambitious CE scenario saves up to 43 Mt CO 2 -eq. compared to the decarbonised baseline scenario, underlining the substantial contribution of CE to decarbonisation. These savings are mainly due to CE practices related to reduce (33% of decrease) strategies. Meanwhile, reuse (8%) and recover (3%) strategies are less effective, given the high annual inflow of construction materials compared to the outflow. The sensitivity analysis addressing epistemic uncertainty increases the robustness of these results, as CE practices in all alternative futures show higher GHG savings than merely decarbonising the energy system. Moreover, narratives containing shrinking economies match or supersede the GHG savings of the default ambitious CE scenario. The discussion on agency then underlines the importance of a strong state and financial incentives to ensure the implementation of reduce practices. Conclusions CE practices are readily available technologies that can support decarbonisation beyond the frequently suggested carbon capture and storage. pLCA scholars, policymakers and practitioners are advised to include more contextualised and diverse socio-economic scenarios in their assessments, based on structured narratives and a participatory process. Such scenarios enable the analysis of uncertainties that go beyond data uncertainty propagation and capture the agency of affected actors who ultimately need to implement the identified solutions.